Comparison of different diagnostic techniques in Plasmodium falciparum cerebral malaria - Fatima Shujatullah, Abida Malik, Haris M. Khan & Ashraf Malik (Journal of Vector Borne Diseases, 2006)
Background & objectives: Plasmodium falciparum cerebral malaria remains a major health problemin India. The efficacy of treatment of cerebral malaria lies in its early diagnosis through rapid diagnosticmethods. ParaSights-F test detects HRP-2 antigen secreted by parasitised red blood cells andquantitative buffy coat assay (QBC) is examination of buffy coat for the presence of malarial parasitestained with acridine orange. This study was performed to evaluate the effectiveness of ParaSight-F test and QBC assay as diagnostic methods in the patients of cerebral malaria.Methods: Fifty clinically diagnosed patients of cerebral malaria were included in the study.ParaSight-F test, QBC and conventional blood smear examination was done. Patients who were incoma and there were no obvious features of bacterial or viral etiology were investigated for cerebralmalaria by these diagnostic methods.Results: ParaSight-F test, QBC and peripheral blood smears were examined. Patients were followedupfor signs of clinical recovery. ParaSight-F test was positive in 47 patients, QBC in 46 while bloodsmear examination was positive in 28 cases.Interpretation & conclusion: Sensitivity and specificity of ParaSight-F test were found to be 96.6 and94% while QBC showed 97.8 and 100% respectively. ParaSight-F test and QBC were found to be novelmethods for diagnosis of cerebral malaria especially in the cases where diagnosis can not be made byconventional blood smear examination due to low parasitaemia. These rapid diagnostic methods helpin early therapeutic intervention.